Analisis Kawasan Andalan di Jawa Tengah - Pujati, Amin (Jurnal Ilmiah Aset, 2009)
This research aims to identify a region as a key region in Central Java . The data was got from the Indonesian Central Bureau of Statistics in 2001 and 2005. The analysis is used klassen typology, location quotient and regional specialization. Klassen typology result can be concluded that the district with the growth of Gross Domestic Regional Bruto and Gross Domestic Regional Bruto per capita are high than other district which have high economic position growth. The result analysis of location quotient, the basic sector in a key region tends to dominate by the secondary and tertiary sector. Index regional specialization result, the district which included in a key region tends to be high than the undeveloped region. Index regional specialization result inter key region tends to the diversification sector. While, between a key region and undeveloped region tends to the specialization sector and inter undeveloped region.